Correlation between depressive symptom and executive function decline in amyloid positive mild cognitive impairment: Neuropsychiatry and behavioral neurology/Mild cognitive impairment/Early symptomatic disease. (7th December 2020) - Choo, IL Han; Chung, Ji Yeon; Chong, Ari; Ha, Jung‐Min; Choi, Yu Yong; Kim, Hoowon
Abstract: Background: V Depression is a risk factor of Alzheimer's disease dementia. We aimed to explore the correlation between depressive symptom and neuropsychological test results in mild cognitive impairment by amyloid positivity. Method: Sixty‐eight individuals with MCI were recruited. All participants received a Clinical Dementia Rating score of 0.5 and met the Petersen's criteria. Comprehensive neuropsychological assessment was performed using the SNSB II. The [18F]Florbetaben PET and MRI scans were performed. T1‐weighted MR 3D volumes were acquired for co‐registration with PET. All participants underwent Geriatric depression scale (GDS). Participants were classified as amyloid positive when the mean cortical SUVR was 1.20 and over. Correlation analyses between GDS score and each neuropsychological test standard score (z‐score based on age‐, education‐, and gender specific normative information) were performed. Result: Significant negative correlation between GDS score and Rey Complex Figure Test Copy z score was found in all MCI participants (r = ‐0.299, p = 0.013). For amyloid positive MCI group (n = 30), we found GDS scores were significantly correlated with Rey Complex Figure Test Copy z score (r = ‐0.364, p = 0.048) and Trail Making Test A z score (r = ‐0.473, p = 0.008). However, for amyloid negative MCI group (n = 39), there was no significant correlation. Conclusion: Our results suggest that amyloid positive MCI patients have significant correlation between depressive symptoms and executive function decline.